Fabrication of Lead Titanate PbTiO3 Nanofiber Mats Via Electrospinning. (31st July 2014) - Šutka, Andris; Timusk, Martin; Kisand, Vambola; Šutka, Anna; Dauksta, Edvins
Abstract : We report an electrospinning approach to producing PbTiO3 polycrystalline nanofibers. The influence of the polymer concentration in the solution on the obtainable PbTiO3 nanofiber morphology was investigated. Nanofibers were characterized by high‐resolution scanning electron microscopy (HR‐SEM) and Raman spectroscopy. After annealing at 500°C for 3 h, the continuous structure of nanofibers remained intact. Only tetragonal PbTiO3 was identified by Raman spectroscopy. Piezoelectric behavior of PbTiO3 nanofiber mats was demonstrated by making a nanomat‐based voltage generator with peak output voltage >1 V.